The Protective Effect of Amorphophallus oncophyllus against Indomethacin-Induced Duodenal Mucosal Injury in Rats via Inhibition of Inflammatory Cell Infiltration - Yuani Setiawati; Rochmah Kurnijasanti; Annette D'Arqom; Jusak Nugraha; Oski Illiandri; Sri Agus Sudjarwo (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Non-steroidal anti-inflammatory drugs (NSAIDs) can cause significant gastrointestinal mucosal injury, particularly in the duodenum. This damage is often initiated by localized erosion of the duodenal mucosa, which triggers a subsequent inflammatory cascade. The porang tuber (Amorphophallus oncophyllus) is a promising candidate for mitigating this injury due to its rich composition of bioactive compounds, including flavonoids, alkaloids, tannins, and glucomannan, all of which possess known anti-inflammatory properties. This study investigated the protective effect of an ethanolic A. oncophyllus extract on the duodenal mucosa in an indomethacin-induced rat model. Thirty Wistar white rats (Rattus norvegicus) were randomly assigned to five groups: a vehicle control, a model group receiving indomethacin, and three treatment groups that were pretreated with A. oncophyllus extract at doses of 50, 100, and 200 mg/kg, respectively, for seven days before a single dose of indomethacin. Our findings demonstrated that the A. oncophyllus extract, particularly at a dose of 200 mg/kg, effectively reduced duodenal mucosal injury caused by indomethacin. This protective effect is likely attributable to the extract's phytochemical profile, which contains flavonoids, tannins, saponins, terpenoids, and alkaloids. In conclusion, this research confirms that A. oncophyllus extract has the potential to protect the duodenal mucosa from NSAID-induced damage.